Effect of physical activity education on shoulder girdle pain and muscle strength in participants with fibromyalgia: a pilot experimental study - Couëpel, Bastien; Daneau, Catherine; Tremblay, Mathieu; Javelot, Thomas; Abboud, Jacques; Pagé, Isabelle; Descarreaux, Martin (Frontiers in Pain Research, 2024)
Background In patients with fibromyalgia, exercise and education are recommended to decrease pain level and improve pain management. The latest scientific evidence recommends to focus interventions on the upper limb. The aim of this pilot study was to compare the immediate effect of physical activity education vs. a control group on pain and muscle capacity in fibromyalgia patients. Method Fifty-six participants with fibromyalgia were randomized into an experimental group and a control group. The intervention consisted in watching a five-minute video that provided information about fibromyalgia, pain, kinesiophobia and physical activity. The control group watched a neutral five-minute video about beavers in Quebec. Following the video, participants performed a muscular fatigue task consisting of a repeated unilateral shoulder abduction task. At baseline and following the muscular fatigue task, maximal voluntary contraction (MVC) in shoulder abduction was assessed as well as pain level and pressure pain threshold (PPT) in the upper limb. Electromyographic activity was also assessed for upper trapezius and middle deltoid muscles. Two-way repeated measures analysis of variance was used to compare the MVC, PPT, and pain level before and after the muscular fatigue task between groups. Results The experimental group showed a significantly lower increase in pain than the control group in the middle deltoid muscle (p = 0.002) when assessed by verbal pain rating scale. No significant interaction or main effect of Group and Time were observed for the pain level at the upper trapezius and elbow extensor muscles nor for any of the PPT measures. According to electromyographic data, the median frequency values indicate that neither group experienced muscle fatigue during the repeated contraction task. Conclusions The preliminary results suggest that a short physical activity education video positively influenced middle deltoid pain following repeated abduction in participants with fibromyalgia. Electromyographic analysis showed no evidence of objective muscle fatigue, suggesting that there might be a partial disconnection between the perception of muscle fatigue and the physiological biomarkers associated with muscle fatigue.